Investigation on different types of blood glucose control system - Gopalakrishnan, Siva; Ummu Kulthum, Jamaludin (Penerbit UiTM, 2017)
Basically it is a case study on proposed blood glucose protocols. Among the protocols been implemented in Intensive Care Unit or critically ill patients were been studied and the outcome of this project is to propose the suitable blood glucose protocol for critically ill patients in Malaysia. Two main protocols known as HTAA and SPRINT been implement in Hospital Tengku Ampuan Afzan Malaysia and Christchurch Hospital, New Zealand respectively. Besides of studying whether both protocols are capable to reduce the mortality rate, these two are compared in terms of patients suitability whether they can adapt to the current protocols or not. Next to find out whether both protocols are same in their goal and the significant level of the patient’s data obtained from both hospitals (HTAA and Christchurch). In order to find out the patients data is significant or not and the goal of the protocols whether similar, some statistical analysis been carried out solidify the hypothesis statement. This is to ensure the outcome statement of proposing the best protocol between HTAA and SPRINT to critically ill patients in Malaysia.